2023
DOI: 10.1007/s10853-022-07405-3
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation-based high-temperature plasticity of polycrystalline perovskite SrTiO3

Abstract: Dislocation networks have been demonstrated to substantially enhance functional properties. As-sintered samples are virtually devoid of dislocations, new innovative techniques for introducing sufficiently high dislocation densities into polycrystalline ceramics are needed. While dislocation-based plasticity at high temperatures has been demonstrated for a large range of ceramic single crystals, plasticity in polycrystals is much less understood. Here, we demonstrate plastic strains in excess of several % based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Although the volume fraction of such regions may be very small, their presence in electroceramic oxides can influence, if not govern, the materials' overall behaviour. In polycrystalline samples of the model electroceramic oxide 1 SrTiO 3 , for example, grain boundaries change the material's plasticity, 2,3 alter its superconductive properties, 4,5 give rise to varistor behaviour, [6][7][8] facilitate resistive switching, 9 and strongly increase its electrical resistance. 7,8,[10][11][12][13][14][15][16] The latter effect in particular is characteristic of grain boundaries across a variety of ionic and mixed ionic-electronic conducting electroceramics, such as systems based on CeO 2 , [17][18][19][20] ZrO 2 , 19,[21][22][23] LaGaO 3 , 24,25 BaZrO 3 , [26][27][28][29][30] and BaCeO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the volume fraction of such regions may be very small, their presence in electroceramic oxides can influence, if not govern, the materials' overall behaviour. In polycrystalline samples of the model electroceramic oxide 1 SrTiO 3 , for example, grain boundaries change the material's plasticity, 2,3 alter its superconductive properties, 4,5 give rise to varistor behaviour, [6][7][8] facilitate resistive switching, 9 and strongly increase its electrical resistance. 7,8,[10][11][12][13][14][15][16] The latter effect in particular is characteristic of grain boundaries across a variety of ionic and mixed ionic-electronic conducting electroceramics, such as systems based on CeO 2 , [17][18][19][20] ZrO 2 , 19,[21][22][23] LaGaO 3 , 24,25 BaZrO 3 , [26][27][28][29][30] and BaCeO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, through thermal activation, new dislocation sources 34,35 can be activated, and the dislocation mobility can also be increased with temperature within the ductile regime of STO 33 . Porz et al 24 . reported that polycrystalline STO could withstand more than 4% plastic strain without fracture during a bulk uniaxial compression test performed above 1050°C.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, through thermal activation, new dislocation sources 34,35 can be activated, and the dislocation mobility can also be increased with temperature within the ductile regime of STO. 33 Porz et al 24 reported that polycrystalline STO could withstand more than 4% plastic strain without fracture during a bulk uniaxial compression test performed above 1050 • C. They also observed a three orders of magnitude increase in the dislocation density (between the pristine ∼ 6 × 10 9 ∕m 2 and deformed sample ∼ 3 × 10 12 ∕m 2 ) using an ultrahigh voltage electron microscope in the scanning transmission electron microscope mode. 24 Similarly, high-temperature dislocation studies on polycrystalline MgO over a broad temperature range (800-1400 • C) revealed that at temperatures between 800 and 1200 • C, dislocation glide governs the plastic deformation.…”
mentioning
confidence: 95%
“…Mechanical loading methods, different from the techniques mentioned above, could introduce dislocations with controllable networks and densities into ceramics, and thus, they have received more attention recently. 7,11,[26][27][28][29][30][31] Hofling et al 13 and Porz et al 32 reported that after high-temperature compression, dislocations with directions aligned with the slip planes could be obtained in BaTiO 3 and STO crystals. However, owing to the brittleness of ceramics, mechanical compression can only produce narrow slip bands with limited dislocation density.…”
Section: Introductionmentioning
confidence: 99%
“…Hofling et al 13 . and Porz et al 32 . reported that after high‐temperature compression, dislocations with directions aligned with the slip planes could be obtained in BaTiO 3 and STO crystals.…”
Section: Introductionmentioning
confidence: 99%